On Three Axiom Systems for Classical Mereology - Varzi, Achille C. (Logic and Logical Philosophy, 2018)
We correct an error and expose two redundancies in the axiom systems presented by Paul Hovda in his 2009 influential paper, ‘What is classical mereology?’.